Introduction to Pasture-Raised Poultry: Getting Started - Brad Burbaugh; Elena Toro; Abel Gernat (EDIS, 2010)
AN232, a 6-page illustrated fact sheet by B. Burbaugh, E. Toro, and A. Gernat, identifies the characteristics of alternative poultry production, explains the opportunities and challenges associated with pasture based production systems, provides an overview of breed selection for egg-type laying hens and meat-type birds, and discusses the equipment and practices that facilitate getting birds off to a good start. Includes references. Published by the UF Department of Animal Sciences, January 2010.